Swedish electoral data: County council elections 1988 - Statistics Sweden (Statistics Sweden, 1989)
Election results for the county council elections in 1976 for all electoral districts in Sweden. Contains information on the total number of eligible voters, number of foreign citizens eligible to vote, number of voters, number of valid and invalid ballots and the number of votes for the major parties.

Valresultat för landstingsvalen 1988 för alla valdistrikt i Sverige. Innehåller uppgifter om totala antalet röstberättigade, antal röstberättigade utländska medborgare, antal röstande, antal giltiga respektive ogiltiga valsedlar samt antalet röster för de större partierna.
Svenska valdata: Landstingsvalen 1988
Keywords: elections; val; election data; valdata; Elections; Val; Social Sciences; Samhällsvetenskap